EFFECT OF SELENIUM AND BRASSINOLIDE ON GROWTH AND YIELD OF TWO BROCCOLI HYBRIDS, BRASSICA OLERACEA VAR. ITALIC (British Journal of Global Ecology and Sustainable Development, 2022)
The experiment was carried out during the agricultural season (2021-2022) in one of the agricultural fields in the village of Tarjeel, Laylan district in Kirkuk governorate, and the experiment included the study of three factors, the first factor included spraying with selenium at concentrations (40, 30, 20 mg.L-1) and the second factor spraying with brassinolide in concentrations 150, 100, 50 mg.L-¹) and factor III hybrids (Paraiso, Jassmine F1). The treatments were sprayed in two batches, the first spray 20 days after planting the seedlings on 1/9/2021, and the second spray 20 days after the first spray. The experiment included three replicates, and each replicate had 14 experimental units. The experiment was implemented according to the Split Plot Design system within the design of randomized complete sectors. R.C.B.D and the data were statistically analyzed according to the least significant difference L.S.D at the probability level of 0.05, where the results showed that spraying with selenium concentration (20 mg.L⁻¹) was significantly superior to the characteristic of the number of leaves, which amounted to 44.430 (leaf ⁻¹) and also the concentration (40 mg.L⁻¹). for the weight of the lateral pink tablets (g), which reached 0.590 g, while the brassinolide at a concentration (100 mg.L⁻¹) was significantly superior in the relative content of chlorophyll in leaves and leaf area of one leaf, which reached (101,335CCI and 632.500 cm² leaves⁻¹) sequentially. While the Jasmine F1 hybrid showed significant superiority, the highest plant height was 75.524 cm, the number of leaves reached 49.733 leaves, the leaf area per leaf reached 693.400 cm² leaf⁻¹, and the lateral flower discs weighed 0.623 g), while the Hybrid Paraiso in traits (The weight of the main disc is 0.756 g and the relative content of chlorophyll in the leaves reached CCI98, 229). As for the dual interactions between the hybrid Jassmine F1 and spraying with selenium at a concentration of 20 mg.L⁻¹, it gave the highest plant height of 79.800 cm, while the hybrid Jassmine F1 and spraying with brassinolide at a concentration were superior. 100 mg.L-1 in (the leaf area of one leaf was 754.700 cm² leaf-1, the number of leaves per plant was 54,330 leaf-¹, the height of the plant was 79.800 cm, and the weight of the lateral flower discs was 0.740 g). The Paraiso hybrid and spraying with brassinolide at a concentration of 100 mg.L⁻¹ were significantly superior to the relative content of chlorophyll in the leaves, which recorded the highest rate of 120, 000 CCI.